Recovery of Post-Pandemic Tourist Visits Rates Through Geopark Destination Attributes - Hidayah, Riski Taufik (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – The Pongkor National Geopark has a geological peculiarity in the form of an underground gold mine that distinguishes it from other geoparks in Indonesia and the world. The Pongkor National Geopark raised the theme of the evolution of the quarter magmatic arc associated with Pongkor gold mineralization as an icon of geological heritage known to the world. The presence of Geopark status shows that the Pongkor area has prominent geological elements and fulfils archaeological, ecological and cultural values ​​and is able to encourage and empower local communities to contribute in maintaining and improving the function of natural heritage so as to contribute to economic development. However, the COVID-19 pandemic has reduced tourist visits as a consequence of the government's efforts to reduce the spread of the outbreak through closing and restricting tourist areas. The purpose of this study was to analyse the effect of destination attributes on the intention of tourist loyalty in the Pongkor National Geopark Area. The method used in this research is verification with the population, namely tourists who have visited the Pongkor National Geopark at least 1 time and are willing to make visits in the future. The analytical method used is Spearman rank correlation, coefficient of determination, and t test with a significance level of five percent. Findings – This research supports previous studies where there is an influence given by the attributes of the destination on the intention of tourist loyalty. The magnitude of the effect given by the destination attribute on loyalty intentions is 57.6%.